Risk factors and costs of household perspectives in hemodialysis patients on Hospital Of Bhayangkara Tk. I. R. Said Sukanto - Anggelina Aprilia Pangalila; Prih Sarnianto; Shirly Kumala (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
The incidence and prevalence of chronic kidney disease (CKD) patients in Indonesia is increasing every year. In the promotion of health promotion and prevention efforts, data related to risk factors and cost analysis are needed from the perspective of patients and / or families related to CKD treatment that requires replacement therapy for kidney function (Hemodialysis / HD). CKD patients undergo HD therapy generally twice a week, making it a relatively large burden on them. This study aims to determine the risk factors for CKD in hemodialysis patients at Bhayangkara Hospital Tk. I R. Said Sukanto and the impact of the cost of HD therapy from a household perspective. In an observational study with this case control method. Primary data was taken through interviews using a structured questionnaire with 100 HD patients (cases) and 100 patients from other poly (control), cross sectional. Risk factor analysis was carried out by logistic regression (p <0.05) and cost analysis using the accounting method. The results showed that in terms of socio-demography, ages above 40-49 years had a risk of 32.7 times and ≥ 50 years had a risk of 17.9 times having CKD compared to <30 years of age with an education level ≤ SD-SMA at risk 16.9 times affected by CKD from the academy / university group, and the income of Rp. 2,000,000 - Rp. 4,000,000 has a risk of 8.4 times being affected by CKD from income groups> Rp. 6,000,000. In terms of biophysiology, hypertension, diabetes and anemia had a risk of 516 times, 54 times and 272 times the effect of CKD. The habit of consuming Chinese and Western herbs increases the risk of developing CKD up to 10.9 times. The cost of the household perspective issued by the patient includes a meal cost of Rp360,000, transportation costs Rp.320,000 and drugs and multivitamins Rp250,000. The potential loss of productivity reaches Rp1,241,904 per patient per month.